Class representation in modern fiction and film - Gandal, Keith (Palgrave Macmillan, 2007)
Rich girl meets poor boy who liberates her then dies. Or, low-life girl is trashed by lower-life boy. The contemporary middle-class fictions of poverty that inform films such as Titanic and Kids are a far cry from the nineteenth-century genres: rags-to-riches stories and seduction tales. Our fictions of class turn the older tales upside down. By the surprising juxtaposition of recent films and the classic writings and unusual lives of Zora Neale Hurston, Stephen Crane, Henry Miller, and Michel Foucault, the book shocks the reader into a reappraisal of these authors works and lives, our myths about class, and poststructural theory.